Tracking blue catfish: quantifying system-wide distribution of a mobile fish predator throughout a large heterogeneous reservoir - Gerber, Kayla M. (Kansas State University, 2015)
A flexible distribution is an adaptive response that allows animals to take advantage of spatial variation in the fluctuation of resources. Distribution of mobile organisms is complex so multi-metric patterns derived from dynamic distribution trajectories must be deconstructed into simpler components for both individuals and populations. Tagging and tracking fish is a very useful approach for addressing these fisheries research questions, but methodological challenges impede its effectiveness as a research tool. Here, I developed and evaluated a high-retention, high-survival tagging methodology for catfish. Then, I integrated multiple distribution metrics to identify if sites within an ecosystem function differently for mobile predators. Finally, I determined if distinct groups of individuals existed, based on distributional patterns. In the appendices, I test sources of variation in system-wide detections (i.e., season, diel period, size, and release location) and provide additional details on methods and interpretation of the results. To address these objectives, I tracked 123 acoustically tagged (VEMCO V9-V13) Blue Catfish (Ictalurus furcatus mean: 505.3 mm TL; SE: 12.3 mm; range: 300-1090 mm) from June through November, 2012-2013, in Milford Reservoir, KS. Across the five months, 85.4-100.0% of the tagged Blue Catfish were detected at least once a month by an array of 20 stationary receivers (VR2W), a detection rate much higher than rates reported in the literature for catfish (38%). Blue Catfish were consistently aggregated in the northern portion of the middle region of Milford Reservoir. Using three metrics (population proportion, residence time, and movements), I found four types of functional sites that included locations with (i) large, active aggregations, (ii) exploratory/transitory functions, (iii) small, sedentary aggregations, and (iv) low use. I also found that tagged Blue Catfish clustered into three groups of individuals based on distribution. These included (1) seasonal movers, (2) consistent aggregations across seasons, and (3) fish exhibiting site fidelity to Madison Creek. Sites with different functions and groups of individual fish were related but not the same. My approach to looking at multiple responses, functions of sites, and individual groupings provided new insights into fish ecology that can advance fisheries management of mobile predators.
Keywords: Blue Catfish; Distribution; Reservoir; Telemetry; Tagging methodology; Fisheries; Biology (0306); Ecology (0329)